Offshoring and Skill-upgrading in French Manufacturing: A Heckscher-Ohlin-Melitz View - Juan Carluccio; Alejandro Cu\~nat; Harald Fadinger; Christian Fons-Rosen (Center for Economic Studies and ifo Institute (CESifo), 2015)
We present a factor-proportions trade model in which heterogeneous firms can offshore intermediate inputs subject to fixed offshoring costs. In the skill-abundant country, high-productivity firms offshore a larger range of labor-intensive inputs to the labor-abundant countries than low-productivity firms. Differently from the traditional versions of factor-proportions trade theory, Heckscher-Ohlin forces operate at the within-industry level, leading to endogenous variation in skill intensity across firms that is positively correlated with firm productivity. Using French firm-level data for the years 1996 to 2007, we provide empirical support for the factor proportions channel through which offshoring to labor-abundant countries affects the firm-level skill intensities of French manufacturers.
Keywords: F11; F12; F14; 330; offshoring; heterogeneous firms; firm-level factor intensities; Heckscher-Ohlin